Evaluating Digital Rehabilitation Outcomes in Chronic Musculoskeletal Conditions Across Non-Obesity, Obesity, and Severe Obesity - Pereira AP; Janela D; Areias AC; Molinos M; Tong X; Bento V; Yanamadala V; Cohen SP; Correia FD; Costa F (Journal of Pain Research)
Ana P Pereira,1,* Dora Janela,1,* Anabela C Areias,1 Maria Molinos,1 Xin Tong,2 Virgílio Bento,1 Vijay Yanamadala,1,3,4 Steven P Cohen,5,6 Fernando Dias Correia,1,7 Fabíola Costa1 1Sword Health, Inc, Draper, Utah, USA; 2Department of Psychology, University of Virginia, Charlottesville, VA, USA; 3Department of Surgery, Quinnipiac University Frank H. Netter School of Medicine, Hamden, Connecticut, USA; 4Department of Neurosurgery, Hartford Healthcare Medical Group, Westport, Connecticut, USA; 5Northwestern Feinberg School of Medicine, Chicago, Illinois, USA; 6Walter Reed National Military Medical Center, Uniformed Services University of the Health Sciences, Bethesda, Maryland, USA; 7Neurology Department, Centro Hospitalar E Universitário Do Porto, Porto, Portugal*These authors contributed equally to this workCorrespondence: Fabíola Costa, Sword Health Inc, 13937 Sprague Lane Ste 100, Draper, UT, 84020, USA, Tel +1 385-308-8034, Fax +1 801-206-3433, Email f.costa@swordhealth.comBackground: Obesity is a known risk factor and aggravator of musculoskeletal (MSK) conditions. The rising prevalence of obesity calls for scalable solutions to address MSK conditions in this population, given their complex clinical profile and barriers to accessing care.Purpose: To evaluate the engagement and clinical outcomes of a fully remote digital care program in patients with MSK conditions, focusing on those with and without comorbid obesity.Patients and Methods: A post-hoc analysis of a prospective, longitudinal, single-arm observational home-based study conducted between August, 2023, and August, 2024. Adults suffering from chronic MSK pain were categorized according to their body mass index (BMI) into non-obesity, obesity and severe obesity. Outcomes included completion rates, engagement, satisfaction, pain (minimal clinically important change: 30%), impairment in daily activities, and patient global impression of change (PGIC). Depending on the clinical outcomes, latent basis growth analysis and logistic regression were used.Results: Completion rates were high across all groups (77.5– 85.6%), although slightly lower in the obesity groups. Fairly similar engagement was observed with both exercise sessions and the educational content (1.9– 2.2 exercise sessions per week; 8.10– 9.31 educational content videos watched). Obesity groups interacted more with the physical therapists than the non-obesity group (severe obesity: 24.6 (SD 10.1); obesity: 23.2 (SD 10.46) vs non-obesity: 22.4 (SD 9.8), P < 0.001). Despite higher baseline risk and clinical impairment in the obesity groups, all groups showed significant pain reductions, with pain responder rates ranging from 56.6 to 63.6%, slightly lower in the severe obesity group. Improvements in daily activities were significant across groups, alongside a positive PGIC (50.4– 53.6%). Satisfaction was very high (> 9/10) in all BMI groups.Conclusion: Despite worse baseline clinical presentations, obesity groups achieved high completion rates, engagement, and significant clinical improvements comparable to the non-obesity group, highlighting the potential of a digital program for this population.Plain Language Summary: Obesity is a common risk factor for musculoskeletal conditions. With obesity rates rising, it is important to find scalable ways to help people with musculoskeletal conditions who are also dealing with obesity, especially since these patients often face challenges in accessing care. Digital telerehabilitation has emerged as an alternative to improve care access, while promoting similar results to in-person care, but its suitability to manage patients with both musculoskeletal and obesity conditions remains underexplored. This study evaluated the suitability of a fully remote digital care program for patients with musculoskeletal conditions, both with and without obesity. We analyzed data from a study of patients with chronic pain, grouping them by body mass index (BMI) into non-obesity, obesity, and severe obesity. Completion rates were high for all BMI groups (77.5– 85.6%), though slightly lower for people with obesity. Despite patients with obesity starting the program with more severe pain and limitations, all groups showed significant reductions in pain. Improvements in daily activities were seen across all groups, and over half of the participants reported positive changes in their condition. Satisfaction with the program was very high in all groups (over 9 out of 10). In conclusion, the remote digital care program was effective for patients with musculoskeletal conditions, including those with obesity, helping them achieve high participation and significant clinical improvements. This study highlights the potential of digital care to effectively manage musculoskeletal conditions among patients with obesity.Keywords: body mass index, physical therapy, telerehabilitation, ehealth, pain